From independence towards freedom Indian women since 1947 - Ray, Bharati (Ed.); Basu, Aparna (Ed.) (Oxford Oxford University Press, 1999)
The twelve essays in this volume highlight the relationship between the Indian nation and its women. They explore the presence, and participation of women in national life in post-independence India. Several indicators of social change. Maternal mortality
Keywords: Women-India; Women in politics; Women-Legal status, Laws etc